2022
DOI: 10.3390/su141710483
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Price Prediction Based on Combined Forecasting Model under Spatial-Temporal Influencing Factors

Abstract: Grain product price fluctuations affect the input of production factors and impact national food security. Under the influence of complex factors, such as spatial-temporal influencing factors, price correlation, and market diversity, it is increasingly important to improve the accuracy of grain product price prediction for agricultural sustainable development. Therefore, successful prediction of the agricultural product plays a vital role in the government’s market regulation and the stability of national food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…In comparison to stacked models and multiple regression, model performance is lower at predicting values, as seen by higher MAPE values approximately 11% observed of SVR for 15 days of average prediction. Most of the researchers have focused LSTM (long short-term memory) (2,4) , Neural network (20) , which needs a huge amount of data as compared to the meta-model presented in the current study, and Traditional statistical approaches like ARIMA, SARIMAX (3,5,11) , which required high computing capacity of classical Machine learning models such as autoregressive models, Feature engineering is performed manually and not able to learn more complex data patterns ultimately. Almost all the published research work reported improvement in accuracy with Bi -Direction LSTM.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison to stacked models and multiple regression, model performance is lower at predicting values, as seen by higher MAPE values approximately 11% observed of SVR for 15 days of average prediction. Most of the researchers have focused LSTM (long short-term memory) (2,4) , Neural network (20) , which needs a huge amount of data as compared to the meta-model presented in the current study, and Traditional statistical approaches like ARIMA, SARIMAX (3,5,11) , which required high computing capacity of classical Machine learning models such as autoregressive models, Feature engineering is performed manually and not able to learn more complex data patterns ultimately. Almost all the published research work reported improvement in accuracy with Bi -Direction LSTM.…”
Section: Resultsmentioning
confidence: 99%
“…An increase in differential order will take more time to run models like ARIMA, SARIMAX. (2)(3)(4)(5)11,20) and Logarithmic Complexity increases with the SARIMAX, Same doesn't apply to LSTM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The three models are implemented on the preprocessed data and evaluated based on the values obtained by comparing metrics and their accuracy in predicting future sales [12]. The performance of each model is compared using metrics such as MAE, RMSE, and MAPE.…”
Section: Objectivementioning
confidence: 99%
“…That is, a feature can only fuse the information contained in the two pieces of data before and after it, but not the information of the data separated from it directly. In this paper, we combined ERNIE-Gram and TextGCN for modeling [ 22 , 23 , 24 ]. Feature extraction was performed using ERNIE-Gram for Chinese, taking into full consideration the relationship between coarse-grained and fine-grained data.…”
Section: Related Workmentioning
confidence: 99%